2006
DOI: 10.1016/j.aap.2005.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic accidents among alcohol-dependent patients: The effect of treatment

Abstract: It is well known that driving under the influence of alcohol increases the risk of traffic accidents. Alcohol-dependent patients are responsible for two-thirds of motor vehicle crashes involving alcohol. Studies carried out on the general population have shown a relation between alcohol dependence and traffic accidents.The aim of the study is to analyse the effect on traffic accidents of treatment of patients with alcohol-related problems. To do so, the prevalence of traffic problems in a sample of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Based on the findings of the present study, traumatic injuries in men were more than women, although this difference was not statistically significant. The results are consistent with other studies [12][13][14][15] because men are more likely to work outside and, therefore, more at risk of accidents. The results of our study also showed that in both sexes, the age group of 30-40 years had the highest rate of traumatic injuries, which are consistent with the findings of the other studies [16][17][18].…”
Section: Discussionsupporting
confidence: 93%
“…Based on the findings of the present study, traumatic injuries in men were more than women, although this difference was not statistically significant. The results are consistent with other studies [12][13][14][15] because men are more likely to work outside and, therefore, more at risk of accidents. The results of our study also showed that in both sexes, the age group of 30-40 years had the highest rate of traumatic injuries, which are consistent with the findings of the other studies [16][17][18].…”
Section: Discussionsupporting
confidence: 93%
“…There is a growing body of evidence that demonstrates that treatment can reduce recidivism and produce beneficial client outcomes (Eibner et al, 2006;Finkbiner & Wisdom, 2004;Gomez-Talegon & Alvarez, 2006;Nochajski & Stasiewicz, 2002;Pratt et al, 2000;Wells-Parker et al, 1995).…”
mentioning
confidence: 98%
“…It was hypothesized that AVC would be associated with greater subsequent PTSS and that AVC and AUD history would interact such that the relationship between AVC and PTSS would be stronger for those with versus without an AUD history. In addition, individuals with BACs ≥ 0.08 during the MVA were examined in separate analyses, given that a high proportion of individuals with AUDs were anticipated to belong to this subset (Gómez-Talegón & Alvarez, 2006; Lapham et. al., 2001).…”
mentioning
confidence: 99%